INOVASI DAN KREATIVITAS UMKM KAMPUNG KLASARI DALAM MENGOLAH SAGU MENJADI TEPUNG DAN KUE - Ahmad Dwi Ghozali; Abdul Azis Khoiri (LPPM IAIN Sorong, 2026)
This study aims to analyze the innovation and creativity of micro, small, and medium enterprise (UMKM) actors in Kampung Klasari in processing sago into flour and various sago-based cake products. The study employs a qualitative method with a descriptive approach, targeting the residents of Kampung Klasari as the primary subjects in the management and processing of sago. The research activities were carried out over the course of one full month, involving 11 students participating in the Community Service Program (KKN) as community facilitators in the production, training, and product development processes. Data collection techniques included participatory observation, in-depth interviews, and documentation. The findings indicate that the community of Kampung Klasari experienced an improvement in skills related to processing sago into flour and a variety of cakes, and demonstrated creativity in terms of flavor variations, shapes, and product packaging. This program has had a highly satisfying positive impact on local residents, as evidenced by increased knowledge, self-confidence, and economic potential within the community through the strengthening of sago-based UMKM